Songs of the Serbian people : from the collections of Vuk Karadžić - Karadžić, Vuk Stefanović, 1787-1864.; Holton, Milne; Mihailovich, Vasa D. (Pittsburgh, Pa. : University of Pittsburgh Press, 1997)
In the early nineteenth century, Vuk Karadzic, a Serb scholar and linguist, collected and eventually published transcriptions of the traditional oral poetry of the South Slavs. It was a monumental and unprecedented undertaking. Karadzic gathered and heard performances of the rich songs of Balkan peasants, outlaws, and professional singers and their rebel heroes. His four volumes constitute the classic anthology of Balkan oral poetry, treasured for nearly two centuries by readers of all literatures, and influential to such literary giants as Goethe, Merimee, Pushkin, Mickiewicz, and Sir Wal.
Porča of Avala and Vuk, the Fiery DragonThe Division of the Jakšićes; The Wife of Hasan Aga; Janko Jurišić; 6. The Songs of Outlaws; Predrag and Nenad; Old Novak and Knez Bogosav; The Captivity of Stojan Janković; The Wedding of Ljubović's Sister; The Death of Ivo of Senj; Old Vujadin; 7. The Songs of the Serbian Insurrection; The Beginning of the Revolt Against the Dahijas; The Battle on Mišar; Selected Bibliography.
Includes bibliographical references (pages 307-310).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Translated from the Serbo-Croat.
Keywords: Karadžić, Vuk, -- 1787-1864.; Epic poetry, Serbian -- Translations into English; Folk songs, Serbo-Croatian -- Texts; Chansons folkloriques serbo-croates -- Textes; 18.58 Serbo-Croatian language and/or literature; LITERARY COLLECTIONS -- General; POETRY -- General; HISTORY -- Europe -- Russia & the Former Soviet Union; Epic poetry, Serbian; Folk songs, Serbo-Croatian; Volkslied; Anthologie; Servo-Kroatisch.; Epic poetry, Serbian; Folk songs, Serbo-Croatian -- Texts; Serbisch; poetry; epic poetry; Texts; Translations; Translations (form); Folk songs (texts); Epic poetry; Folk poetry; Folk songs; Musical texts; Poetry; Poésie épique.; Poésie populaire; Chansons folkloriques; Paroles (Musique); Poésie.